Revitalisasi dan Konservasi Permukiman Tua Kota Balikpapan Sebagai Identitas Kota - Mahagarmitha, Rilia Rigina (RUAS, 2022)
The development of a city can be influenced by several things, including the geographical location and the condition of the natural resources of the region or area, one example is the city of Balikpapan whose development was initiated by the presence of petroleum natural resources, so that until now the city of Balikpapan is still known as "Oil City". Another advantage that makes the development of the city of Balikpapan is faster because it is supported by the geographical condition of the city of Balikpapan so that it becomes more strategic and is used as a stopover place both between cities and between provinces. As a stopover, the characteristics that can become the identity of a region are very important. To realize this, this research was carried out, using descriptive and qualitative methods in analysis and discussion. From the results of the analysis, it is known that it is necessary to maintain the physical form of an area, especially those that have historical values in the course of city development, one of which is by revitalizing and conserving areas in the city.